Contribution of active faults in the intraplate area of Iberia to seismic hazard: The Alentejo-Plasencia Fault - Villamor, P.; Capote, R.; Stirling, M.W.; Tsige, M.; Berryman, K.R.; Martínez-Díaz, J.J.; Martín-González, F. (Journal of Iberian Geology, 2012)
We present the earthquake potential characterisation of the Alentejo-Plasencia Fault (APF) in the intraplate area of the Iberian Peninsula. The APF displays clear deformation of geomorphic surfaces and sediments of Neogene and younger age and, thus, we consider it to be active within the current tectonic regime. APF fault slip rate values range from 0.01 to 0.1 mm/yr with a preferred value of 0.05 mm/yr. Mw associated to fault rupture ranges from 6.6 to 8.7 using different segmentation models (segments ranging from 20 to 500 km) and various fault scaling relationships. Recurrence intervals derived from slip rate and Mw range from 10 ka to 4 Ma, with preferred values between 20 and 30 ka. Other faults in the interior of Iberia present similar values. Hazard curves produced using all fault sources from the intraplate Iberia show that active faults of the intraplate Iberia do not contribute significantly to seismic hazard at short return periods typical of the building codes ( 500 year return periods). However, they can be important contributors to hazard at critical facilities (high hazard dams, nuclear power plants, emergency response buildings) where return periods of interest may be 10,000 years or more. Our fault source characterisation is very preliminary (with large uncertainties) and further detailed studies of active faults across the whole plate boundary are required to confirm the values for the intraplate faults presented here.